Temporalis myofascial flap for head and neck reconstruction in Chiang Mai University Hospital - Tananuvat, Rak; Raunmakeaw, Donyarat (Biomedical Sciences and Clinical Medicine, 2018)
Objective To determine the effi cacy and long-term results of temporalis myofascial flap (TMF) reconstruction of head and neck defects. Methods This is a retrospective review of 28 consecutive patients who had undergone head and neck surgery and reconstruction by TMF at Chiang Mai University Hospital over the period January 2005 through March 2010. Associated factors contributing to postoperative complications and longterm results were also studied. Results A total of 28 patients were recruited with an average age at surgery of 55.25±11.63 years. Sixteen patients had nasal cavity and maxillary sinus cancer, 6 had oral cavity and oropharyngeal cancers, 3 had parotid cancer, 1 had cementifying fi broma, 1 had facial palsy, and 1 had osteoradionecrosis of the mandible. The complication rate was 17.9%. Two patients (7.1%) had total flap loss and one (3.6%) had partial flap loss. The minor complication rate was 10.7%. None of the patients had zygomatic bone exposed during the follow-up period and none experienced frontal branch palsies after flap elevation. There were no serious complications of the donor site. Conclusion TMF is an effective technique for head and neck reconstruction with a low rate of complications. It provides a safe and well vascularized flap with less donor site morbidity and dysfunction and can be used to reconstruct many surgical defects of the mid-facial and adjacent area. TMF is an alternative to free flap reconstruction and can be used in combination with other flaps. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />